Quality deterioration of bananas in the post-harvest supply chain- an empirical study - Indika Fernando; Jiangang Fei; Roger Stanley; Hossein Enshaei; Alieta Eyles (Modern Supply Chain Research and Applications, 2019)
Purpose-Qualitydeteriorationinbananasalongthesupplychain(SC)duetocosmeticdamagehasbeena persistent challenge in Australia. The purpose of this paper is to investigate the incidence of cosmetic defectsin bananas across the post-harvest SC and determining the causesof thediminished fruitquality at the retail stores. Design/methodology/approach - The study quantified the level of cosmetic damage in 243 cartons of Cavendishbananasacrossthreepost-harvestSCsinAustraliafrompackhousestoretailstoresandidentified the risk factors for cosmetic defects. Findings- Thelevelofcosmeticdamageprogressivelyincreasedfrompackhouse(1.3percent)todistribution centre(DC)(9.0percent)andretail(13.3percent)andwassignificantlyinfluencedbypackageheightandpallet positioningduringtransit.Abrasiondamageinripenedbananaswasinfluencedbythetraveldistancebetween DC and retail store. The study also revealed a range of risk factors contributing to the observed damage including weakened paperboard cartons due to high moisture absorption during the ripening process. Research limitations/implications - This study only investigated damage incidence in three post-harvest banana SCs in Australia and the damage assessments were confined to packaged bananas. Originality/value - This study assessed the quality of bananas along the entire post-harvest SC from farm gate to retail store. The study provided knowledge of the extent of the quality defects, when and where the damage occurred and demonstrated the underlying factors for damage along the SC. This will enable the development of practical interventions to improve the quality and minimize wastage of bananas in the retail markets.
Keywords: 650; Quality; Supply chain; Banana; Mechanical damage; Post-harvest